La reconnaissance dans les organisations. Précisions terminologiques - Béatrice Vacher; Yanita Andonova (Communication)
This is an attempt to clarify the terminology used to study the “subject” within organizations. This attempt is approached through a reading of past and current theories centred on the issue of recognition. Partial answers to the following questions are offered: To what and to whom do we refer when speaking of recognition? How does recognition better articulate the bond between the individual and the collective? Why is recognition of such importance when, presently, the borders between the private and the professional spheres become porous?